Conservative management of a severe case of onychocryptosis at a podiatric clinic—A case report - Jakubowska, Michalina; Wcisło‐Dziadecka, Dominika (Journal of cosmetic dermatology, 2022)
Background Onychocryptosis, also known as ingrown toenails or ungues incarnati, is a fairly frequent condition, with global prevalence of approximately 20%. Objectives This study is aimed at discussing possible conservative management of severe onychocryptosis, with a case report. Methods Conservative approach is effective in reducing or even entirely correcting underlying nail deformities. Eliminating nail fold inflammation is necessary prior to the bracing procedure. The non‐surgical approach combined with proper wound treatment of the involved nail folds is a promising alternative for a growing number of patients. Results Nail plate deformities may be largely corrected or fully eliminated. As demonstrated by our case report, even advanced stages of onychocryptosis may be effectively treated with nonsurgical modalities. Conclusion Proper podiatric care facilitates conservative approach to management of ingrown toenails, improving the patient's overall wellbeing and eliminating pain. The prerequisite for nonsurgical correction of the nail plate is treating inflammation first. Conservative correction is more aesthetically pleasing and less emotionally disturbing to the patients than partial or complete surgical avulsion. Lesser invasiveness is an advantage especially in the case of patients with chronic comorbidities.